Heat treatment effect on the evolution of magnetic properties of martensite in magnetic shape memory Ni48Mn39.5Sn9.5Al3 Heusler alloy ribbons. (March 2021) - Czaja, P.; Przewoźnik, J.; Fitta, M.
Graphical abstract: Highlights: Ground magnetic martensite state in Ni48 Mn39.5 Sn9.5 Al3 ribbon has been studied. Martensite is superparamagnetic at intermediate temperature range. Blocking temperature evolves in response to thermal treatment. Novel, magnetic hard phase singled out by exchange bias appears below 80 K. Abstract: The magnetic ground state of martensite in Ni48 Mn39.5 Sn9.5 Al3 ribbons shows considerable complexity and a two stage behavior. Initially, below the blocking temperature it evolves from a superparamagnetic state into a frozen state with a strong ferromagnetic component and it manifests some spin glass like characteristics. The ferromagnetic component is sensitive to thermal treatment, what stems from its susceptibility to variation in the retained ferromagnetic austenite fraction, change in the degree of order as well as the density of ferromagnetic/antiferromagnetic domain interfaces. At temperatures below 80 K, a divergence from linear correspondence to the Almeida-Thouless law signifies that the system enters into a magnetically harder and inhomogeneous state distinguished by exchange bias.